SISTEM PAKAR DIAGNOSA PENYAKIT SAPI POTONG DENGAN METODE NAIVE BAYES - Indriana Candra Dewi; Arief Andy Soebroto; Muhammad Tanzil Furqon (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2015)
In order to produce quality beef, one of the important factors in maintenance of cattle is to maintain the health of livestock to stay fit. One way to provide an understanding of the breeders is to use expert system. An expert system is one of the artificial intelligence which is adopting of the expert knowledge that used to solve problem that usually can only be solved by expert in the field. Expert systems can be allowed to extend the working range of experts so that expert knowledge can be acquired and used anywhere. In this expert system use a Naive Bayes method as inference methods for diagnosing the disease. Types of diseases that can be recognized by expert system are 11 types of disease while symptoms that can be recognized the expert system are 20 types of symptom. The results of testing the accuracy of the 26 test case data, have generated the level of conformity percentage of 96,15%.